2021
DOI: 10.1093/ajcn/nqaa447
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Schisandra chinensis Baillon extracts and regular low-intensity exercise on muscle strength and mass in older adults: a randomized, double-blind, placebo-controlled trial

Abstract: Background Studies suggest that Schisandra chinensis Baillon (Sc) may enhance muscle strength and mass because of its anti-inflammatory and antioxidant properties. Objectives We aimed to examine the effects and safety of consumption of Sc extract (SCe) for 12 wk on muscle strength and mass in older adults with relatively low muscle mass who do low-intensity exercise. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 31 publications
0
42
0
4
Order By: Relevance
“…Subjects of the following criteria will be considered to have dropped out or discontinued participation in the trial and will be excluded from the per-protocol analysis: failure to take the IOE supplementation or placebo for five consecutive days, failure to attend follow-up assessments, and poor compliance (< 80%). This study protocol is similar to our previously published study (13).…”
Section: Participant Recruitment and Screeningmentioning
confidence: 76%
“…Subjects of the following criteria will be considered to have dropped out or discontinued participation in the trial and will be excluded from the per-protocol analysis: failure to take the IOE supplementation or placebo for five consecutive days, failure to attend follow-up assessments, and poor compliance (< 80%). This study protocol is similar to our previously published study (13).…”
Section: Participant Recruitment and Screeningmentioning
confidence: 76%
“…On the contrary, the current study was conducted for 12 weeks. The number of subjects for whom statistical power was calculated based on a prior study ( 19 ) was included. Both men and women were included, and the supplement dosage was slightly increased.…”
Section: Discussionmentioning
confidence: 99%
“…We used MedCalc version 19.4.1 (MedCalc Software Ltd., Ostend, Belgium) to calculate the sample size, which was based on a similar earlier study ( 19 ). The estimated sample size was 18 subjects per group for 80% power to detect a difference of 4.36 Nm mg/dL in average knee extension peak TQ at an angular velocity of 60°/s, assuming an SD of 4.6 Nm in the primary outcome variable and an α error of 5%.…”
Section: Methodsmentioning
confidence: 99%
“…However, recently published studies seem to view 1 g/day as the optimal dose. Cho et al reported that SCs supplementation (1 g/day) can enhance skeletal muscle strength but not mass in older adults who perform low-intensity exercise [ 42 ]. In addition, the results of Jang et al have shown that supplementation with SC (1 g/day) may help to improve QMS and decrease lactate levels in adult women [ 17 ].…”
Section: Discussionmentioning
confidence: 99%